Related Factors of Internet Addiction on Adolescents During COVID-19 Pandemic : Systematic Literature Review - Kusnadi, S.Psi, Annisa Puti; Kaloeti, M.Psi, Psikolog, Dr. phill. Dian Veronika Sakti (Universitas Ahmad Dahlan, 2022)
The increase in youth internet use occurred during the COVID-19 pandemic. This study aims to examine internet use and the factors that cause internet addiction in adolescents during the COVID-19. This study uses the Preferred Reporting Items for Systematic Review and Meta-Analysis 2015 in conducting a systematic literature review using the Scopus, ScienceDirect, Pubmed, Emerald Insight databases. There were ten articles that met the inclusion criteria and passed the article quality assessment. The results of the study found that resilience, self efficacy, self esteem, gender, mental health, difficulty sleeping, fear of COVID-19, and loneliness are internal factors that influence internet addiction in adolescents. While the duration of internet use, limitations of social interaction, family roles including parental education, family harmony, control, and family function, socioeconomic level, online learning, social support, and social emotional adjustment are external factors that influence adolescents in developing Internet addiction. Future research can examine internet addiction prevention interventions by considering related factors found in this study. Keywords: Adolescents, Covid-19, Factors, Internet Addiction, Parents